2013
DOI: 10.1002/star.201300133
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of α‐amylase via adsorption onto bentonite/chitosan composite: Determination of equilibrium, kinetics, and thermodynamic parameters

Abstract: Immobilization of α‐amylase onto bentonite/chitosan (BC) composite was studied via adsorption. The composite was characterized by FTIR, SEM, and surface area measurements. The effect of different factors such as, pH, temperature, initial enzyme concentration, and various thermodynamic parameters was determined. The maximum α‐amylase adsorption capacity of the BC composite was determined as 64 mg/g at 0.8 mg/mL enzyme concentration. The activity of the immobilized enzyme was measured under varying experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
3
15
0
2
Order By: Relevance
“…The Langmuir adsorption capacity, Q max was 55.56/100 mg support, while the Freundlich adsorption capacity, K was 8.88/100 mg support. The 1/ n value is a scale of the surface heterogeneity and may have a value between 0 and 1, becoming more heterogeneous as its value gets closer to zero . The results show that the Langmuir adsorption model fitted the experimental data better ( R 2 = 0.963) than the Freundlich model ( R 2 = 0.899).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The Langmuir adsorption capacity, Q max was 55.56/100 mg support, while the Freundlich adsorption capacity, K was 8.88/100 mg support. The 1/ n value is a scale of the surface heterogeneity and may have a value between 0 and 1, becoming more heterogeneous as its value gets closer to zero . The results show that the Langmuir adsorption model fitted the experimental data better ( R 2 = 0.963) than the Freundlich model ( R 2 = 0.899).…”
Section: Resultsmentioning
confidence: 88%
“…The adsorption of enzymes on solid supports is the oldest, simplest, and easiest method of immobilization. The simplicity of the procedure, the cost, and the fact that the initial activity of the enzyme is maintained to a considerable degree make this method suitable in commercial production .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the enzyme concentration (mg/mL), the volume of loaded enzyme (µL/bead), the activation time (h), and the incubation time on the adsorption of α‐amylase onto the chitosan beads were investigated. The adsorption process was monitored by following the decrease of the α‐amylase concentration by ultraviolet absorbance at 280 nm . The adsorption efficiency of α‐amylase onto the beads was determined as follows: q=(C0C)C0×100 where q is the percentage of α‐amylase adsorbed onto the beads (mg/100 mg), C 0 and C are the initial and final α‐amylase contents, respectively (mg).…”
Section: Methodsmentioning
confidence: 99%
“…However, the variation of the optimal pH value upon immobilization was different. In previous studies [22,27], free and immobilized a-amylases had optimal activities at the same pH value although the enzymatic stability in relation to the change of the pH value was improved for the immobilized form. The observed discrepancy might be due to the structural reconstruction of the enzyme molecules.…”
Section: The Effect Of the Ph Value On The Relative Activitymentioning
confidence: 96%
“…Protein adsorption is very complicated process driven by different protein-surface forces, such as hydrophobic, electrostatic, and ionic interactions; van der Waals forces; or hydrogen bonds; and the temperature dependency of these forces is different from each other. 34,35 Effect of temperature on the adsorption process was studied at five different temperatures (5-40 • C). As seen in Figure 5, maximum cellulase adsorption was observed at 25 • C. It was observed that the maximum cellulase adsorption onto p(HEMA-MAPA) cryogel was increased slightly (8.9%) by increasing temperature from 5 to 25…”
Section: Effect Of Temperaturementioning
confidence: 99%